RANCANG BANGUN ALAT PENGEPRES MINYAK KACANG TANAH (Arachis hypogaea L.) SEMI MEKANIS (Design and Construction of Semi Mechanic Peanut (Arachis hypogaea L.) Oil Press) - Nico Pakpahan; Saipul Bahri Daulay; Nazif Ichwan (Universitas Sumatera Utara, 2019)
ABSTRACT Compression process is one step of getting oil from the plant, such as peanut . The postharvest processing’s purpose is to make the agricultural product have a higher economic value compared to the product without processed. The purpose of this research was to design, build and test of semi mechanic peanut oil press. The parameters observed were effective capacity, and economic analysis.The results showed that the effective capacity was 2,79 kg/hour. Main cost in the semi mechanic oil press was Rp 3041,18/kg for first year; Rp 3047,62/kg for the second year; Rp 3054,06/kg for the third year; Rp 3061,12/kg for the fourth year and Rp 3068,69/kg for fifth year. BEP in the semi mechanic peanut oil press was 135,22 kg for first year; 141,96 kg for the second year; 149,09 kg for the third year; 156,71 kg for the fourth year and 164,85 kg for fifth year. NPV at 6,5% semi mechanic peanut oil press was Rp 66.087.806,07/year and internal Rate of Return of this equipment was 45,9 %. Keywords: peanut, pressing tool, peanut oil. ABSTRAK Pengepresan merupakan salah satu cara untuk mengambil minyak yang terdapat pada tumbuhan, salah satu contohnya kacang tanah. Proses pengolahan pascapanen bertujuan agar hasil pertanian memiliki nilai ekonomis yang lebih tinggi dibandingkan sebelum dilakukan pengolahan. Penelitian ini bertujuan untuk mendesain, membuat dan menguji alat pengepres minyak kacang tanah semi mekanis. Parameter yang diamati yaitu kapasitas efektif alat dan analisis ekonomi.Hasil penelitian menunjukkan bahwa kapasitas efektif alat sebesar 2,79 kg/jam. Biaya pokok alat pengepres minyak kacang tanah semi mekanis Rp 3041,18/kg untuk tahun pertama; Rp 3047,62/kg untuk tahun kedua; Rp 3054,06/kg untuk tahun ketiga; Rp 3061,12/kg untuk tahun keempat dan Rp 3068,69/kg untuk tahun kelima. BEP pada alat pengepres minyak kacang tanah semi mekanis sebesar 135,22kg pada tahun pertama; 141,92kg pada tahun kedua; 149,09kg pada tahun ketiga; 156,71kg pada tahun keempat dan 164,85kg pada tahun kelima. NPV alat pengepres minyak kacang tanah semi mekanis pada suku bunga 6,5% sebesar Rp 66.087.806,07/tahun dan nilai internal rate of return alat ini adalah sebesar 45,9 %. Kata kunci: kacang tanah, alat pengepres, minyak kacang tanah.